2017
DOI: 10.1016/j.bpj.2017.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Imaging of a Single Gene Reveals Transcription-Initiated Local Confinement

Abstract: Genome dynamics are intimately linked to the regulation of gene expression, the most fundamental mechanism in biology, yet we still do not know whether the very process of transcription drives spatial organization at specific gene loci. Here, we have optimized the ANCHOR/ParB DNA-labeling system for real-time imaging of a single-copy, estrogen-inducible transgene in human cells. Motion of an ANCHOR3-tagged DNA locus was recorded in the same cell before and during the appearance of nascent MS2-labeled mRNA. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
187
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 174 publications
(221 citation statements)
references
References 64 publications
34
187
0
Order By: Relevance
“…Interestingly, the explored volume of the Rad23a TSS barely changed during the entire reprograming process. Taken together, these findings, are consistent with previous super-resolution imaging works suggesting that the mobility of the promoter is constrained upon activation 36,37 .…”
Section: Resultssupporting
confidence: 92%
“…Interestingly, the explored volume of the Rad23a TSS barely changed during the entire reprograming process. Taken together, these findings, are consistent with previous super-resolution imaging works suggesting that the mobility of the promoter is constrained upon activation 36,37 .…”
Section: Resultssupporting
confidence: 92%
“…The presence of a population with close to 0.5 in both conditions is indicative of a ground-state Rouselike chromatin fiber architecture [30,31]. Upon serum stimulation, anomalous diffusion became predominant and its value ( ~ 0.33) is indicative of entangled polymers [32], and was seen for a single labelled site [13]. The entanglement could effectively be established by random DNAcrosslinking by protein complexes, as became also apparent from polymer simulations inspired by chromosomal capture data [33].…”
Section: Transcription Status Modulates Chromatin Diffusion Processesmentioning
confidence: 99%
“…It is now becoming increasingly clear that such nuclear compartments are also dynamic entities whose formation and maintenance over time is of great interest in order to understand the mechanisms and function of genome folding [9]. Tracking of labelled single DNA loci [10][11][12][13][14] or chromatin domains [15,16] demonstrated that chromatin motion is highly heterogeneous at short time intervals. However, sparse loci are difficult to place in the context of global chromatin organization and its enduring configurational changes [17].…”
Section: Introductionmentioning
confidence: 99%
“…Spreading is not only integral to the partition process but has also enabled use of ParB/S systems as an alternative to fluorescent repressor-operator systems (FROS) for visualization of genetic loci in bacteria [1,2]. We have developed them for use in eucaryote cells and viruses as the ANCHOR system (3)(4)(5). They offer certain advantages over FROS: the weakness of ParB oligomerization and DNA binding interactions allows other chromatin-based processes to disperse the complexes easily, making them less disruptive than FROS, and the small number of integrated parS binding sites involved is less locally intrusive than the hundreds typical of FROS.…”
Section: Introductionmentioning
confidence: 99%